2020
DOI: 10.1007/s00264-020-04762-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of thigh pain following total hip arthroplasty with short, tapered-wedge stem

Abstract: Purpose: The occurrence of thigh pain following cementless total hip arthroplasty (THA) may be dependent on multiple factors, which may differ with design of the prosthesis. Thus, this study aimed to investigate the frequency of thigh pain following cementless THA using a short, tapered-wedge stem to identify risk factors for thigh pain.Methods: This retrospective cohort study analysed 222 joints of patients who underwent THA with a short, tapered-wedge stem. Thigh pain was evaluated using a questionnaire duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…On the other hand, Vidalain JP reported that thigh pain was observed in only 2 out of 127 hips at 20 years postoperatively using the Corail stem, and the rate was similar to the results of the present study. In addition, although cortical hypertrophy, where the cortical bone becomes thicker when stress is concentrated at the distal part of the stem has been reported to correlate to thigh pain in THA using short tapered-wedge stem 18 , no cortical hypertrophy was observed with either Corail or Hydra stem in this study. These results may be considered to be in line with the concept of the Corail type fully HA-coated stems, where the load is distributed on the entire body of the stem.…”
Section: Discussioncontrasting
confidence: 70%
“…On the other hand, Vidalain JP reported that thigh pain was observed in only 2 out of 127 hips at 20 years postoperatively using the Corail stem, and the rate was similar to the results of the present study. In addition, although cortical hypertrophy, where the cortical bone becomes thicker when stress is concentrated at the distal part of the stem has been reported to correlate to thigh pain in THA using short tapered-wedge stem 18 , no cortical hypertrophy was observed with either Corail or Hydra stem in this study. These results may be considered to be in line with the concept of the Corail type fully HA-coated stems, where the load is distributed on the entire body of the stem.…”
Section: Discussioncontrasting
confidence: 70%
“…The occurrence of thigh pain impairs the restoration of hip function, occasionally resulting in revision surgery; however, this is a common complication following THA (21,22). Thigh pain was previously reported in 16.7% of 222 patients after THA using the short tapered-wedge stem (23), and thigh pain was reported by 18.9% of 95 patients with the short tapered-wedge stem in this study. In contrast, thigh pain did not occur in 133 patients with the conventional full HA compaction stem at the 11.5-year follow-up (24), and 83% of the patients were completely symptom-free at the 20-year follow-up (25).…”
Section: Discussionmentioning
confidence: 48%
“…Symptoms caused by pathological load transfer around the tip of the stem are ultimately an exclusion diagnosis after other causes have been ruled out carefully. On conventional radiographs, pathological load transfer can be postulated when cortical hypertrophy is noted around the tip of the stem in combination with proximal stress shielding 10,26,27 . A bone scan might be used as an additional tool to further investigate this condition.…”
Section: Discussionmentioning
confidence: 99%